2022
DOI: 10.11646/zootaxa.5190.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography, Speciation and Taxonomy within the genus Bactrocera Macquart with application to the Bactrocera dorsalis (Hendel) complex of fruit flies (Diptera: Tephritidae: Dacinae)

Abstract: The genus Bactrocera Macquart comprises a large group of some 750 species distributed across the Asia-Pacific and Afrotropical regions. Most of these have been described and revised by Drew (1989), Drew & Hancock (1994) and Drew & Romig (2013, 2022). A taxonomic study of such a large and diverse group of species provides valuable information that can be used in the elucidation of concepts on biogeography and evolution that are presented in this paper. While a wider discussion of this genus and its many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
0
5
0
2
Order By: Relevance
“…But Drew and Romig proposed the withdrawal of this result (Drew and Romig, 2016). Further evidence based on the male aedeagus showed that B. phillipinensis and B. invadens differed from B. dorsalis (Drew et al, 2022), confirming this withdrawal. Our results show that B. dorsalis is more closely related to B. thailandica than B. phillipinensis and B. invadens (Figure 2; Supplementary Figures S9-S11).…”
Section: Phylogeny Of the Fruit Fliesmentioning
confidence: 55%
“…But Drew and Romig proposed the withdrawal of this result (Drew and Romig, 2016). Further evidence based on the male aedeagus showed that B. phillipinensis and B. invadens differed from B. dorsalis (Drew et al, 2022), confirming this withdrawal. Our results show that B. dorsalis is more closely related to B. thailandica than B. phillipinensis and B. invadens (Figure 2; Supplementary Figures S9-S11).…”
Section: Phylogeny Of the Fruit Fliesmentioning
confidence: 55%
“…Lalat buah (Bactrocera spp) berpotensi dalam menurunkan hasil produksi usaha tani (Drew & Hancock, 2022). Serangan lalat buah mengakibatkan kerugian baik dari sisi kualitas maupun kuantitas hasil produksi dengan intensitas serangan mencapai 100% (Kaurow et al, 2015) sehingga dapat menyebabkan gagal panen.…”
Section: Pendahuluanunclassified
“…Selain itu, Tanaman cabai merupakan tanaman inang utama dari spesies Bactrocera dorsalis (Al Rahmat et al, 2021). Sedangkan, Bactrocera carambolae menyerang tanaman cabai walaupun bukan tanaman inang utama, tetapi spesies lalat ini memiliki sifat polifag atau dapat hidup lebih dari satu tanaman inang (Drew & Hancock, 2022). Jenis lalat buah yang memiliki sifat polifag pada fase bertelur akan meletakan telurnya ke dalam buah.…”
Section: Identifikasi Jenis Lalat Buahunclassified
“…Bactrocera philippinensis , B. papaya , and B. invadens were previously considered junior synonyms of B. dorsalis ( Schutze et al., 2015 ; Zeng et al., 2019 ). Nonetheless, Drew and Hancock (2022) have delineated them as distinct entities from B. dorsalis based on differences in the shapes and dimensions of the glans and preglans appendix. The maggot of B. dorsalis poses the most significant threat, with adult females utilizing their spiny ovipositors to penetrate the fruit skin and laying eggs beneath the rind.…”
Section: Introductionmentioning
confidence: 99%